Urban schistosomiasis: An ecological study describing a new challenge to the control of this neglected tropical disease - Elainne Christine de Souza Gomes; Iris Edna Pereira da Silva; Wheverton Ricardo Correia do Nascimento; Rodrigo Moraes Loyo; Ana Lúcia Coutinho Domingues; Constança Simões Barbosa (Elsevier, 2022)
Summary: Background: Social and environmental vulnerabilities contribute to the persistence and increase of Schistosomiasis, which has been a public health problem in Brazil and worldwide. In this study, we aimed to monitor the entry, installation, and maintenance of schistosomiasis transmission in an urban area on the Brazilian coast over two decades (2000-2010/2010-2020). Methods: This population-based cross-sectional study was conducted in Porto de Galinhas, state of Pernambuco, Brazil, to investigate the dynamics of schistosomiasis transmission in the urban area. Through 3 malacological and parasitological surveys and using geoprocessing technologies, schistosomiasis transmission foci (STF), as well as cases of the disease were identified and quantified. Statistical and geoprocessing tools were used to analyse the data. Findings: Overall, the number of STF decreased from 15 (2000) to 11 (2010) and then to 9 (2020). Although the infection ratio of snails in 2000 has decreased from 16·1% to 5·8% in 2010, we observed an increase to 7·2% in 2020. Additionally, 6,499 individuals were analysed (2012 in 2000; 2459 in 2010, and 2028 in 2020) and the prevalence of human infection has decreased over years, from 32·5% (2000), 16·6% (2010) to 8·8% (2020). The disorderly urbanization process was directly related to the spatial distribution of STF and schistosomiasis cases, causing a new scenario where people became infected by walking on unpaved and flooded streets. Interpretation: Although we observed a decreasing in schistosomiasis cases and STF, this NTD became a health problem related to urbanization in the study area. The challenge to overcome this new sort of transmission will require a greater understanding of the disorderly migration, spatial occupation, and degradation of the environment. Funding: National Council for Scientific and Technological Development (CNPq), Ministry of Science, Technology, Innovations and Communications, Brazil.